Brief Lives : Sigmund Freud - Carter, David (London Hesperus Press Ltd., 2011)
Born to Jewish parents in mid-19th-century Austria, Sigmund Freud is a controversial figure needing no introduction, yet his reputation owes as much to myth as to the facts of his life and his work. Here, David Carter uncovers the man buried beneath the mythology, tracing the life of this inimitable figure from his origins as the gifted first born of eight children, through his stellar academic career and his relationships and rifts with famous figures such as Josef Breuer. Also explored is why, despite his groundbreaking work on psychoanalytic theories$1 (Bincluding the functioning of the subconscious, the repression of trauma, and the psychological import of dreams$1 (BFreud has frequently been the subject of derision and ridicule.s
Include Notes and Bibliography.
Keywords: Psychoanalysts -- Austria -- Freud, Sigmund, 1856-1939